Dynamic molecular choreography induced by acute heat exposure in human males: a longitudinal multi-omics profiling study - Wen, Jirui; Cheng, Juan; Wang, Ling; Li, Can; Zou, Yuhao; Wu, Jiang; Liu, Jifeng (Frontiers in Public Health, 2024)
Introduction: Extreme heat events caused by occupational exposure and heat waves are becoming more common. However, the molecular changes underlying the response to heat exposure in humans remain to be elucidated.This study used longitudinal multi-omics profiling to assess the impact of acute heat exposure (50℃ for 30 min) in 24 subjects from a mine rescue team. Intravenous blood samples were collected before acute heat exposure (baseline) and at 5 min, 30 min, 1 h, and 24 h after acute heat exposure (recovery). In-depth multi-omics profiling was performed on each sample, including plasma proteomics (untargeted) and metabolomics (untargeted).Results: After data curation and annotation, the final dataset contained 2473 analytes, including 478 proteins and 1995 metabolites. Time-series analysis unveiled an orchestrated molecular choreography of changes involving the immune response, coagulation, acid-base balance, oxidative stress, cytoskeleton, and energy metabolism. Further analysis through protein-protein interactions and network analysis revealed potential regulators of acute heat exposure.Moreover, novel blood-based analytes that predicted change in cardiopulmonary function after acute heat exposure were identified.This study provided a comprehensive investigation of the dynamic molecular 2 changes that underlie the complex physiological processes that occur in human males who undergo heat exposure. Our findings will help health impact assessment of extreme high temperature and inspire future mechanistic and clinical studies.